PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STUDENTS TEAM ACHIEVEMENT DIVISION (STAD) DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR FISIKA - Suadnyana, I Made (Widyadari: Jurnal Pendidikan, 2019)
Classroom Research activities aims to improve their scores in Physics using educational model Uncooperative Studnts Team Achievement Division (STAD). This research data collected by a gifl test their scores. Analyzing the data analysis methods used by descriptive. Data resulted from prevalency or consists of initial data, data and data cycle I cycle II. From preliminary data, average new class reached 71 and thoroughness learning new reached 28 percent. This Data far below expectations considering KKM asian Physics lessons in this school is 75. At cycle I have already taken place the increase the price class reached 74 and percentage thoroughness learning reached 81 percent In the cycle II average class has reached 79 and the percentage thoroughness learning has reached 88 percent. Data in the cycle II is now hope model of teaching which is a result of the use nature konstruktivis. The conclusions is model of teaching method Uncooperative Studnts Team Achievement Division) can increase (STAD children's learning achievements improve